I can see my virtual body in a mirror: The role of visual perspective in changing implicit racial attitudes using virtual reality - Marini, Maddalena; Casile, Antonino (Frontiers in Psychology, 2022)
Recent studies showed that VR is a valid tool to change implicit attitudes towards outgroup members. Here, we extended this work by investigating conditions under which virtual reality (VR) is effective in changing implicit racial attitudes. To this end, participants were embodied in a Black or White avatar and we manipulated the perspective through which they could see their virtual body. Participants in one condition, could see their virtual body both from a first-person perspective (i.e., by looking down towards themselves) and reflected in a mirror placed in front of them in the VR environment. Participants in another condition could instead see their virtual body only from a first-person perspective (i.e., by looking down towards themselves) as no mirror was placed in the VR environment. Implicit racial attitudes were assessed using the Implicit Association Test (IAT) before and immediately after the VR intervention. Results showed that when White participants were embodied in a Black avatar compared to a White avatar, they showed a decrease in their implicit pro-White attitudes but only when they could see their virtual body both from a first-person perspective and in a mirror. These results suggest that, in immersive virtual reality interventions, the possibility for participants to see their body also reflected in a mirror, might be a critical factor in changing their implicit racial attitudes.